Acetabular Lip Augmentation Devices for the Unstable Total Hip Replacement—A Systematic Review - Fergus J. McCabe, MB BCh, BAO, MCh, MRCSI; Martin Kelly, MB BCh, BAO, MCh, MRCSI; Conor Farrell; Muthana Abdelhalim, MB BCh, MRCSI; John F. Quinlan, MB BCh, BAO, MCh, FFSEM, FRCS (Tr & Orth) (Arthroplasty Today, 2021)
Background: The optimal management strategy for instability afte total hip arthroplasty remains unclear. Acetabular lip augmentation devices may offer an operative solution for recurrent instability. This systematic review reports the clinical outcomes of acetabular lip augmentation devices in comparison to other treatment options. Methods: A literature search strategy was performed of Medline, EMBASE, and CENTRAL on September 19, 2020, for all studies reporting outcomes of acetabular lip augmentation devices for recurrent dislocation after total hip arthroplasty. Non-English language articles were excluded. Clinical and survivorship data were collated and analyzed. Results: Thirteen studies describing acetabular augmentation were included for analysis. A total of 644 hips in 636 patients were augmented with a mean age of 75 years (39 to 103). Five different augmentation devices were used. The posterior lip augmentation device (PLAD, DePuy) was the most used (406 hips). Overall, acetabular lip augmentation devices had a 10% postoperative dislocation rate at a mean follow-up of 49 months (0.2 to 132). The PLAD had a 3.9% subsequent dislocation rate with a mean follow-up of 51 months (0.2 to 132). Only one study compared the PLAD to a dual-mobility cup, which demonstrated shorter operative times with the PLAD but higher rates of dislocation and revision surgery. Conclusion: The quality of literature on lip acetabular augmentation devices is poor. In these studies, the postoperative dislocation rate after lip acetabular augmentation was relatively high. The PLAD (DePuy) has the most evidence and may offer a therapeutic option for recurrent instability, in very specific clinical situations.